Associations between basic motor competencies, club sport participation, and social relationships among primary school children - Johanna Kress; Harald Seelig; Kathrin Bretz; Ilaria Ferrari; Roger Keller; Jürgen Kühnis; Simone Storni; Christian Herrmann (Current Issues in Sport Science, 2023)
Children learn and deepen their motor competencies in a social context. Basic motor competencies (BMC) enable children to actively co-act and participate in sports situations with peers. Participation in club sport activities has a positive influence on the development of motor and social competencies. The purpose of this study is to describe the connection between basic motor competencies, club sport participation and interpersonal relationship skills among 6 to 8 years old children. In the present study, the BMC of N = 880 first and second grade primary school children (48.9% girls, aged M = 90.36 months, SD = 6.90) in Switzerland were tested in the competence domain of self-movement and object movement. The children’s club sport participation and the relationship skills were recorded from the parents’ perspective. Data was analysed using correlations and mixed regressions. The results show a connection between relationship skills, basic motor competencies and club sport participation in school children. For boys, significant correlations were found between relationship skills and BMC (r = .186, p ≤ .01) so as with the club sport frequency (r = .184, p ≤ .01). For girls, only the correlation between relationship skills and club sport frequency (r = .137, p ≤ .01) was significant. The frequency of club sport participation (β = .13, p = .009), motor competencies (β = .09, p = .016) and sex (β = .10, p = .004) of the children were found to be predictors for the relationship skills. The results of this study suggest that children with higher motor competencies and children who participate more often in club sport seem to have better relationship skills. These findings are relevant as they indicate a link between motor competencies and interpersonal relationship skills in middle childhood.